The Beginnings of Political Economy - Backhaus, Jürgen Georg (Springer, 2017)
This volume contains eleven essays on Johann Heinrich Gottlob von Justi's concepts of the modern economy. These essays reflect both Justi's life and professional work, focusing on his ideas on economics and social sciences. Interesting are the aspects of his biography that gave rise to the development of his economic thought. Apart from Justi's personal background, this book contains the beginning of modern economics because Justi's philosophy was linked to government, labour, morality, health and finally the good society.